Thickening Thin Narratives: A Feminist Narrative Conceptualization of Male Anorexia Nervosa - King, David (Narrative Works, 2013)
The purpose of this article is to conceptualize a feminist narrative approach to male anorexia nervosa (MAN). Both narrative and feminist theories have been utilized to enrich the discourse of AN among women. An unintended result of this primary focus on women’s experiences has been a limited focus on the experiences of men with AN. This article will explore a contemporary social discourse on masculinity, why some men utilize AN as a means of attaining the ideals put forth through such discourse, and how a feminist narrative approach can be applied to working with men struggling with AN.